2015
DOI: 10.1007/s11010-015-2383-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide mitigates homocysteine-mediated pathological remodeling by inducing miR-133a in cardiomyocytes

Abstract: An elevated level of homocysteine called hyperhomocysteinemia (HHcy) is associated with pathological cardiac remodeling. Hydrogen sulfide (H2S) acts as a cardioprotective gas, however the mechanism by which H2S mitigates homocysteine mediated pathological remodeling in cardiomyocytes is unclear. We hypothesized that H2S ameliorates HHcy mediated hypertrophy by inducing cardioprotective miR-133a in cardiomyocytes. To test the hypothesis, HL1 cardiomyocytes were treated with: 1) plain medium (control, CT), 2) 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 55 publications
2
37
0
Order By: Relevance
“…The H 2 S donor SG1002 prevents cardiac hypertrophy and cardiac dysfunction by reducing endoplasmic reticulum stress in high-fat diet-fed mice (9). Our laboratory has demonstrated that H 2 S treatment mitigates cardiac hypertrophy by upregulating miR-133a (73), an antihypertrophy (24, 41) and antifibrosis (28, 101) microRNA. To increase the levels of miR-133a, H 2 S activates myosin enhancer factor-2c (MEF2C), a transcription factor of miR-133a, by releasing MEF2C from MEF2C-HDAC1 complex (inactivated state) (73).…”
Section: H 2 S Mitigates Pathological Cardiac Remodeling By Inhibitinmentioning
confidence: 99%
See 2 more Smart Citations
“…The H 2 S donor SG1002 prevents cardiac hypertrophy and cardiac dysfunction by reducing endoplasmic reticulum stress in high-fat diet-fed mice (9). Our laboratory has demonstrated that H 2 S treatment mitigates cardiac hypertrophy by upregulating miR-133a (73), an antihypertrophy (24, 41) and antifibrosis (28, 101) microRNA. To increase the levels of miR-133a, H 2 S activates myosin enhancer factor-2c (MEF2C), a transcription factor of miR-133a, by releasing MEF2C from MEF2C-HDAC1 complex (inactivated state) (73).…”
Section: H 2 S Mitigates Pathological Cardiac Remodeling By Inhibitinmentioning
confidence: 99%
“…Our laboratory has demonstrated that H 2 S treatment mitigates cardiac hypertrophy by upregulating miR-133a (73), an antihypertrophy (24, 41) and antifibrosis (28, 101) microRNA. To increase the levels of miR-133a, H 2 S activates myosin enhancer factor-2c (MEF2C), a transcription factor of miR-133a, by releasing MEF2C from MEF2C-HDAC1 complex (inactivated state) (73). These studies suggest that H 2 S plays a crucial role in inhibiting cardiac hypertrophy (Fig.…”
Section: H 2 S Mitigates Pathological Cardiac Remodeling By Inhibitinmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, hyperhomocysteinemia (HHcy) is suggested as a new and independent risk factor for developing these conditions (38,39). HHcy occurs as a consequence of an impaired remethylation process or a deficiency in Hcy metabolic enzymes [cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE), and 3-mercaptopyruvate sulfur transferase] (19). These three enzymes break down Hcy into hydrogen sulfide (H 2 S) (33).…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S acts as a vasorelaxant (45) and an inhibitor of hypertrophy and fibrosis of vascular smooth muscle cells (17). Taking into consideration that HHcy can be caused by the inhibition of metabolic enzymes that produce H 2 S from Hcy (19), the question arises whether the blockade of H 2 S synthesis influence homocysteine-induced cardiac effects.…”
Section: Introductionmentioning
confidence: 99%